2018
DOI: 10.1515/med-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a neurokinin-1 antagonist in preventing multiple-day cisplatin-induced nausea and vomiting

Abstract: AbstractObjectiveTo perform a prospective non-randomized comparison of the effectiveness and safety of combined neurokinin-1 antagonist aprepitant treatment with the standard multiple-day cisplatin regimen for the prevention of cisplatin-induced nausea and vomiting (CINV).Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…The most common aprepitant-and olanzapine-related AEs included sedation, fatigue and constipation.The occurrences between two groups were identical and it were consistent with other studies examining aprepitant and olanzapine-related AEs [4,8,14] . In general, the tolerability in the study was safe, no grade 3 or 4 adverse events were observed in this study, and no patients discontinued the study because of undesired sedation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common aprepitant-and olanzapine-related AEs included sedation, fatigue and constipation.The occurrences between two groups were identical and it were consistent with other studies examining aprepitant and olanzapine-related AEs [4,8,14] . In general, the tolerability in the study was safe, no grade 3 or 4 adverse events were observed in this study, and no patients discontinued the study because of undesired sedation.…”
Section: Discussionsupporting
confidence: 90%
“…Patients receiving multiple-day cisplatin chemotherapy are at risk of both acute and delayed nausea and vomiting for each day, as acute and delayed emesis may overlap after the initial day chemotherapy until the last day of chemotherapy [1,2] . Although the combination of aprepitant, 5-HT3 receptor antagonist(5-HT3RA) and dexamethasone(DXM) had showed higher complete response than the combination of 5-HT3RA plus dexamethasone in cisplatin multiple-day chemotherapy clinical studies, nausea remains a major problem for many patients [3,4,5] . The activity of olanzapine on multiple receptors, particularly the D2, 5-HT2c and 5-HT3 receptors, may be involved in nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study confirmed a higher CR rate with multi-day chemotherapy than with single-day chemotherapy. 16 Second, the vast majority of patients in the former study were young women, while the present study had more older and male patients, and being both young and female were high-risk factors for CINV, thus possibly leading to a higher CR rate. 17 In this study, the TP rate in both groups reached over 90% in the acute phase but was low in the delayed phase, indicating that prevention and treatment of CINV in the delayed phase might be more difficult and deserves clinical attention.…”
Section: Discussionmentioning
confidence: 58%
“…The previous study confirmed a higher CR rate with multi-day chemotherapy than with single-day chemotherapy. 16 Second, the vast majority of patients in the former study were young women, while the present study had more older and male patients, and being both young and female were high-risk factors for CINV, thus possibly leading to a higher CR rate. 17 …”
Section: Discussionmentioning
confidence: 58%
“…However, a study in mice showed that maropitant administration reduced intestinal motility and delayed intestinal transit time of labeled luminal contents (Mikawa et al, ). Similarly, humans using similar NK‐1 receptor antagonists have reported side effects of constipation in up to 16% of patients studied in one population (Jacob et al, ; Li et al, ). Peer‐reviewed data are unavailable describing intestinal motility disorders associated with maropitant in species other than mice, and further investigation is warranted prior to administering maropitant to horses at risk for gastrointestinal impaction.…”
Section: Discussionmentioning
confidence: 90%